Creation of Information Systems Design on the Concept of "Accessible Environment": Designing Systems Orienting Information in Public Places - A. Kazachkova, O.; ., . (International Journal of Engineering and Technology, 2018)
This article discusses the basic principles of creating an information system design, using the example of navigation in public places, in order to create a space accessible to all categories of people, taking into account the capabilities of people with disabilities. Identified and analyzed the key tasks of the shopping center navigation system, aimed at ensuring the "accessibility" of public places, and its main components. Issues related to factors influencing the design of the navigation system itself and the design of its components, information carriers, are considered.Â Â